The use of Fukuyama's sulfonamide in the synthesis of selectively protected spermidines - Silva Emerson T. da; Fona Fátima S.; Lima Edson L. S. (Journal of the Brazilian Chemical Society, 2004)
The differentiation of terminal amino groups in polyamines usually involves a series of protection and deprotection steps, leading to long reaction sequences with low overall yields. Given the relevance of the biological activities displayed by polyamines, the development of more efficent synthetic routes for these compounds is highly desired. Herein we report the synthesis of two selectively protected spermidines, using Fukuyama's sulfonamide. Both syntheses were performed in three steps, starting from 1,3-diaminopropane, with an overall yield higher than 40%.